Estudo de elastômeros termoplásticos vulcanizados (TPVs) de borracha natural e polipropileno - Rojas, Galia Johanna Alzate (2015)
Natural rubber (NR) is used for the preparation of several articles in domestic, industrial and automotive worldwide. However, for the NR can be used in these applications it must be vulcanized hindering their recyclability, since the material cannot be reprocessed by conventional processing methods. In this context, the development of thermoplastic elastomer (TPE) using NR, which can be processed into products using conventional equipment and processes for thermoplastic materials, ensuring recycling while also adding value to the base material. The proposed objectives were: To study formulations of TPV- (NR + PP) with different reinforcing agents systems (silica, nanosílica and carbon black), vulcanization (sulfur, phenolic resin and dicumyl peroxide) and antioxidant (6PPD + TMQ), evaluating their rheological, thermal, mechanical, morphological and structural properties, and evaluate the recyclability of TPVs. Initially the influence study of materials of TPVs materials was found that the highest values mechanical properties were achieved with PP with melt flow index 11g/10min and NR-TSR-5. It was established that higher values of mechanical properties have been achieved by mixing the ingredients in two steps. The best mechanical properties values were obtained with TPVs (NR + PP) phenolic resin, carbon black and antioxidant (TMQ + 6PPD). Furthermore, the properties are improved by TPVs recycling due to chemical reactions of the phenolic resin with the PP, improving the compatibility in TPVs. The antioxidant system (6PPD + TMQ) considerably improves the behavior of TPVs both recyclability, as the mechanical properties; this behavior is related to the improvement of the compatibility of the NR and PP amines in the presence of the antioxidant system which react with NR.